Air pollution and irritations due to cigarette smoke - Weber-Tschopp, A; Jermini, C; Grandjean, E (Sozial- und Präventivmedizin, 1976)
In a nearly airtight climatic chamber of 30 m3 we studied the air pollution due to cigarette smoke as well as resulting irritations and annoyance. When 9 cig/30 m3 have been smoked, acroleine reaches the threshold limit value for industries; when 5 cig/30 m3 have been smoked, the clean air standards for outdoor air are exceeded by acroleine, carbon monoxide, and formaldehyde. The eyes are the most sensitive organ to cigarette smoke, followed by the nose. Annoyance about air quality and the wish to open the door or to leave the room proved to be other susceptible criteria. With 10 cig/30 m3, 9% of the subjects show a "strong" or "very strong" eye irritation, while 78% "wish to leave the room=. The most important of the measured irritants seems to be acroleine.